2009
DOI: 10.1063/1.3088871
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus ion implantation in silicon nanocrystals embedded in SiO2

Abstract: We have investigated phosphorus ion ͑P + ͒ implantation in Si nanocrystals ͑SiNCs͒ embedded in SiO 2 , in order to clarify the P donor doping effects for photoluminescence ͑PL͒ of SiNCs in wide P concentrations ranging in three orders. Some types of defects such as P b centers were found to remain significantly at the interfaces between SiNCs and the surrounding SiO 2 even by high-temperature ͑1000°C͒ annealing of all the samples. Hydrogen atom treatment ͑HAT͒ method can efficiently passivate remaining interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…9-11 Electron spin resonance measurements have shown that hydrogen annealing removes nonradiatve defects at the Si/ SiO 2 interface, which results in an increase in PL. 9, 10 Cho et al 12 showed that hydrogen passivated Si nanocrystals embedded in silicon nitride have enhanced charge retention characteristics as compared to unpassivated nanocrystals. This was attributed to reduction in charge loss pathways because of hydrogen passivation of the defects at the Si nanocrystal/silicon nitride interface.…”
Section: Influence Of Surface Chemistry On Photoluminescence From Deumentioning
confidence: 98%
“…9-11 Electron spin resonance measurements have shown that hydrogen annealing removes nonradiatve defects at the Si/ SiO 2 interface, which results in an increase in PL. 9, 10 Cho et al 12 showed that hydrogen passivated Si nanocrystals embedded in silicon nitride have enhanced charge retention characteristics as compared to unpassivated nanocrystals. This was attributed to reduction in charge loss pathways because of hydrogen passivation of the defects at the Si nanocrystal/silicon nitride interface.…”
Section: Influence Of Surface Chemistry On Photoluminescence From Deumentioning
confidence: 98%
“…8,9 Therefore, usually very high dopant concentrations are employed. 10,11 Up to now, the main processes used for phosphorus (P) doping of SiNCs in a SiO 2 matrix are the co-sputtering technique [10][11][12] which normally results in a continuous doping of the whole layer, or ion implantation [13][14][15] resulting in a non-uniform dopant depth profile. However, a selected doping of ultra thin layers (either the barrier or the SiNCs containing active layer) during the deposition process is not possible with these methods.…”
mentioning
confidence: 99%
“…This is the reason why this type of process is currently widely used in solar cell production. However, despite its potential application for nanostructure doping such as nano-grains in nc-Si [1,2,4], nanowires [5] or nanocrystals [6,7], atomic transport in nanometric phases is still poorly known. In the case of nc-Si, it has been shown that atomic transport kinetics could be enhanced in nanograins and that triple junction diffusion is several orders of magnitude faster than grain boundary (GB) diffusion [8,9].…”
mentioning
confidence: 99%